PENERAPAN MODEL PEMBELAJARAN JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA MATERI KESEIMBANGAN EKOSISTEM SISWA KELAS VI - Mikail Mikail (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2019)
This study aims to improve the learning outcomes of Grade VI students on natural science subjects with the subject of ecosystem equilibrium using the Jigsaw Cooperative Learning Model. This research is a Classroom Action Research (CAR). The subject of this research is a students of Grade VI Elementary School (SDN) 03 Jereweh with 25 students. This research took place in two cycles consisting of 3 meetings for cycle-1 and 2 meetings for cycle-2. Data collection techniques in this study were observation and tests. Classroom Action Research results by applying the Jigsaw Learning Model shows that student’s natural science learning outcomes have increased. This is indicated by an increase in the average value of the class that is during cycle-1 the average value of 74 increased to 82.6 in cycle-2. Classical completeness of students has increased by 52% from cycle 1 to cycle 2. The conclusion of this study is that the application of Jigsaw Learning Model can improve student learning outcomes in the material ecosystem equilibrium in class VI SDN 03 Jereweh.